Understanding service recovery satisfaction from a service encounter perspective: A pilot study - C. Boshoff (South African Journal of Business Management, 2007)
When a service provider fails to meet the expectations of customers during a so-called service encounter, the resultant disconfirmation can lead to a series of negative outcomes such as defection and negative word-of-mouth. Often, however, errant firms are afforded a second opportunity by complaining customers to rectify their misdemeanours – a practice referred to as service recovery. Service marketers' understanding of service recovery is, however, limited. This study investigates service recovery from a service encounter perspective by considering the influence of what the complaining customer can visually see during the encounter. The underlying premise of the study is that, during the service encounter the complaining customer is exposed to stimuli such as the physical features and appearance of the service provider and these features can influence their assessment of the service firm's efforts to resolve their complaint.By drawing on social psychology theory this study investigates whether what a complaining customer sees during the service encounter (what the service provider looks like) influences their satisfaction with the service recovery efforts of the firm. The empirical results of this pilot study do not support the general contention of the social psychology theories investigated in this study.
Keywords: 650